∫ 1 ∞ x 2 1 ( 2 π ( d x d cos − 1 ( cos ( x π ) ) ) + π ) d x = A
Given the above equation, find ⌊ 1 0 0 0 A ⌋ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
noooooooooooooooo............................
Log in to reply
I'll post actual solution also.. don't worry.
The moment I saw that the question had an unconventional number "306"(not 300 or a multiple of 50) , I felt that I had to try my luck and ....
But you are one great genius , dude . How could you manipulate your question to the desired answer or were you waiting for your followers to get to 306 to post this question ? :P
Log in to reply
I did not, I just got something close to 300 and then waited for the moment :P
Same observation lead to the same guess! I think this is the first such problem I've seen which is not addressed to − − 0 followers...
@Julian Poon Sorry Sir, but I just couldn't resist guessing the answer.
Problem Loading...
Note Loading...
Set Loading...
Of course, everyone's first try will be: 3 0 6 .
A = ∫ 1 ∞ x 2 1 ( 2 π ( d x d cos − 1 ( cos ( x π ) ) ) + π ) d x d x d cos − 1 ( cos ( x π ) ) = ∣ sin x π ∣ π sin x π ⇒ A = ∫ 1 ∞ x 2 1 ( 2 ∣ sin x π ∣ sin x π + 1 ) d x ∵ ∣ sin x π ∣ sin x π = 1 ∀ 2 n < x < ( 2 n + 1 ) a n d ∣ sin x π ∣ sin x π = − 1 ∀ ( 2 n + 1 ) < x < 2 ( n + 1 ) ⇒ A = ∑ i = 1 ∞ ∫ 2 i 2 i + 1 x 2 1 d x ⇒ A = 2 1 − 3 1 + 4 1 − 5 1 + 6 1 − . . . C o n s i d e r : 1 + t t = t − t 2 + t 3 − t 4 + t 5 − . . . ( s u m o f G . P ) ⇒ ∫ 0 1 1 + t t d t = ∫ 0 1 ( t − t 2 + t 3 − t 4 + t 5 − . . . ) d t = 2 1 − 3 1 + 4 1 − 5 1 + 6 1 − . . . b u t ∫ 0 1 1 + t t d t = ∫ 0 1 1 − 1 + t 1 d t = 1 − lo g 2 ⇒ A = 1 − lo g 2 ≈ 0 . 3 0 6 8 ⇒ ⌊ 1 0 0 0 A ⌋ = 3 0 6